Screening for osteoporosis within the region of Doboj using heel bone ultra- sound densitometry - Aleksandra Hadžiavdić; Nikola Gavrić (Биомедицинска истраживања, 2013)
Introduction: . Osteoporosis is a progressive, systemic and metabolic disease of bones that leads to the loss of the bone mineral density as well as to an increased risk of fracture. Aim: of the study is to inves tigate the percentage of osteopenia and osteoporosis in women of various age groups within our region as well as identification of risk factors. Methods: . Heel bone ultrasound densitometry has been done by an ultrasound densitometer (ULTRA - SONOMETER GE LUNAR 1). Research is done with a direct method using a standard procedure. Risk factors are divided into three groups and the results are defined in terms of T-score values. Results: . Research has encompassed 836 patients, out of which 753 (90.1%) are women and 83 (9.9%) are men. Average age of female examinees is 52.6 years. In the first risk group we analyze age structure of the patients, start of menarche, length of menopause, BMI indexes and T-score values. Results: obtained show that there are no significant variations in relation to the epidemiological data mentioned by other sources. Analysis of the T-score values and risk factors of the second group, existence of chronic diseases and use of medicines also show that the results obtained match those of the WHO researches. Results: obtained by analysis of the T-score values and risk factors of the third group, smoking and coffee con sumption do not fit into epidemiological studies performed so far and therefore further studies should go into that direction. Conclusion: . The aforementioned method is very useful when it comes to detection of the status of the bone density as well as undertaking of timely prevention and osteoporosis treatment. It is necessary to put much more effort into general education about osteoporosis in order to reduce its consequences.
Keywords: osteoporosis; prevention; treatment